Letter: a potassium‐competitive acid blocker vs a proton pump inhibitor for healing endoscopic submucosal dissection‐induced artificial ulcers after treatment of gastric neoplasms—authors' reply. Issue 5 (4th August 2017) - Kagawa, T.; Iwamuro, M.; Inaba, T.
Abstract : Linked Content This article is linked to Ban et al and Ugimoto and Kagawa papers. To view these articles visithttps://doi.org/10.1111/apt.14202 andhttps://doi.org/10.1111/apt.13747 .